Correlation between Platelet to Lymphocyte Ratio as Predictive Factor of Neurological Deficit in Acute Ischemic Stroke Patients - Putri, Syarifah Nurus Soffia Perwira; Sasmita, Poppy Kristina; Barus, Jimmy Fransisco Abadinta (PT FORMOSA CENDEKIA GLOBAL, 2025)
Acute ischemic stroke is the most common stroke type, with inflammation and thrombosis playing key roles. The platelet-to-lymphocyte ratio (PLR) has been proposed as a potential prognostic biomarker. To evaluate the association between PLR and neurological deficits or functional outcomes in acute ischemic stroke. A systematic review was conducted using multiple databases. Study quality was assessed with the NewcastleOttawa Scale (NOS), and outcomes were evaluated using NIHSS, mRS, and SSS. Ten studies were included, mostly from Asia. Elevated PLR was significantly associated with poor outcomes, especially in Chinese studies and those with NIHSS